2021
DOI: 10.1017/s1463423621000463
|View full text |Cite
|
Sign up to set email alerts
|

Healing the Past by Nurturing the Future: Aboriginal parents’ views of what helps support recovery from complex trauma

Abstract: We aimed to understand support needs for Aboriginal and Torres Strait Islander parents experiencing complex trauma.Becoming a parent is an exciting yet challenging transition, particularly for parents who have experienced past hurt in their own childhood which can have long lasting effects, including complex trauma. Complex trauma-related distress can make it harder to care for a baby, but the parenting transition offers unique opportunities for recovery. This formative research is part of a community-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…There were 29 studies that reported on the wellbeing of Indigenous youth in Australia [ 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 ]. Our thematic analysis identified seven overarching components of wellbeing for this population: basic needs; relationships; culture; aspirations for the future; identity; recreational activities and interests; and physical and mental health.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There were 29 studies that reported on the wellbeing of Indigenous youth in Australia [ 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 ]. Our thematic analysis identified seven overarching components of wellbeing for this population: basic needs; relationships; culture; aspirations for the future; identity; recreational activities and interests; and physical and mental health.…”
Section: Resultsmentioning
confidence: 99%
“…Tight financial situations can prevent young people from accessing basic needs and extra opportunities, such as sport [ 102 ]. Accessing health services can be easier for youth through community-controlled health clinics [ 82 , 85 , 98 , 101 , 106 , 107 ], however service providers report financial instability remains a barrier to access [ 97 ], and youth may be reluctant to access community clinics due to concerns around their privacy in small communities [ 99 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants in this study were clear that the escalating rates of Aboriginal and Torres Strait Islander children in out‐of‐home care was never far from the minds of parents. Further, the ‘language of trauma’ itself can cause anxiety, and we need to positively reframe this negative language to foster the aspirations, hopes and dreams of parents for a ‘fresh start’ and new life with their baby (Chamberlain et al, 2019b; Chamberlain et al, 2021).…”
Section: Discussionmentioning
confidence: 99%